155k views
2 votes
-
ax + by = c, bx + ay = (1 + c)​

User MVck
by
4.7k points

2 Answers

1 vote

Step-by-step explanation:

ax + by = c, bx + ay = (1 + c)

substituting ax + by to c

bx + ay = 1 + ax + by

bx + ay - ax - by = 1

bx - ax + ay - by = 1

x (b - a) + y(a - b) = 1

x (b - a) - y(b - a) = 1

(x-y)(b-a) =1

User Alex Yan
by
5.8k points
5 votes

Answer and explanation:

ax + by = c, bx + ay = (1 + c)

Because ax + by = c so let sub it into bx + ay = (1 + c)

bx + ay = (1 + c)

bx +ay = 1 + ax + by

Subtract ax and bu from both side, we got:

bx + ay - ax - by = 1

bx - ax + ay - by = 1

We got common term x and common term y, we get:

x (b-a) + y (a-b)

x (b-a) - y (b-a) because when you change the sign, it would also change the sign in the bracket

(x-y)*(b-a) = 1

This is the simpliest form this equation can get

Hope this helped :3

User Kolenda
by
6.3k points